EFFECTS OF TEMPERAMENT ON MILK RELATED TRAITS IN SIMMENTAL DUAL-PURPOSE COWS - Neamt I. Radu; Cziszter T. Ludovic; Saplacan I. Silviu; Mihali V. Ciprian; Mizeranschi E. Alexandru; Daniela E. Ilie (Journal of Animal and Plant Sciences, 2023)
The objective of the current study was to establish a possible link between cows’ reactivity and milk-related traits. In addition, the study intended to examine changes in herd structure related to cow temperament over successive years. Between October 2016 and October 2021, 7600 data were collected from 1520 lactations for milk, fat, and protein yields, as well as milking speed based on cow temperament. The cow’s temperament was classified as calm, moderate, and nervous. Most of the cows exhibited moderate reactivity (87.13%) compared to calm (5.24%) and nervous (7.63%). The one-way ANOVA protocol showed that cow’s reactivity significantly influenced (p≤0.001) milk, fat and protein yields having more substantial effects (p≤0.001) on the milking speed for nervous ones. The calm cows produced more milk (5766.86±130.98 kg), fat (239.12±5.24 kg) and protein (201.56±4.3 kg) compared to moderate (-309.7, -19.73, -15.3 kg, p≤0.01) and nervous cows (-707.9, -32.2, -28 kg, p≤0.01). Significantly higher milking speed was recorded for calm cows (2.36 kg/min.) compared to moderate (2.28 kg/min., p≤0.05) and nervous cows (2.21 kg/min., p≤0.01). Over successive years a significant increased (p≤0.001) trend in calm (from 3.34 to 8.92%) was observed to the detriment of the nervous cows (from 5.45 to 2.32%) and moderate ones (from 91.21 to 88.76%). The current findings highlight that calmer cows produce more milk, fat and protein yields compared to nervous ones despite the controversial relationship between temperament and milk related traits.
Keywords: milk related traits; milking speed; Simmental breed; temperament